2016
DOI: 10.3390/ijms17101706
|View full text |Cite
|
Sign up to set email alerts
|

Drought-Responsive Mechanisms in Plant Leaves Revealed by Proteomics

Abstract: Plant drought tolerance is a complex trait that requires a global view to understand its underlying mechanism. The proteomic aspects of plant drought response have been extensively investigated in model plants, crops and wood plants. In this review, we summarize recent proteomic studies on drought response in leaves to reveal the common and specialized drought-responsive mechanisms in different plants. Although drought-responsive proteins exhibit various patterns depending on plant species, genotypes and stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
147
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(158 citation statements)
references
References 212 publications
(311 reference statements)
9
147
0
2
Order By: Relevance
“…GS activity in the present study remained unchanged in ON66 and YT13 and was slightly reduced in Maali. The GS-GOGAT pathway, implying two key enzymes (GS and GOGAT), is heavily affected by water deprivation [43]. Immunoblottings showed a considerable abundance of GS2 isoform compared with GS1, regardless of the growth conditions ( Figure 5D), which is an accordance with previous findings [8].…”
Section: The Gs-gogat Pathway Is Impacted By the Osmotic Stresssupporting
confidence: 91%
See 2 more Smart Citations
“…GS activity in the present study remained unchanged in ON66 and YT13 and was slightly reduced in Maali. The GS-GOGAT pathway, implying two key enzymes (GS and GOGAT), is heavily affected by water deprivation [43]. Immunoblottings showed a considerable abundance of GS2 isoform compared with GS1, regardless of the growth conditions ( Figure 5D), which is an accordance with previous findings [8].…”
Section: The Gs-gogat Pathway Is Impacted By the Osmotic Stresssupporting
confidence: 91%
“…These drought-responsive mechanisms include gene expression regulation, reactive oxygen species scavenging, carbohydrates metabolism, and nitrogen metabolism [42,43].…”
Section: Differential Growth Performance Of Durum Wheat Genotypes Undmentioning
confidence: 99%
See 1 more Smart Citation
“…Also in bentgrass the expression of a gene encoding dehydrin RAB15 was up-regulated in response to drought stress, which is an ABA and drought induced molecular chaperone [18]. Besides genes involved in the synthesis of plant hormones, signalling pathways, synthesis of osmoprotectants, those that encode the members of the antioxidant system has been also reported to alter upon water deficit [39]. The abundances of peroxidases (PODs) were also increased in the leaves of drought-tolerant rice cultivar [40].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies demonstrated that protein kinases play a crucial role in abiotic stresses such as drought and salinity (Yang et al, 2008). Induced expression and the role of homocysteine Smethyltransferase under drought stress is well studied (Kale et al, 2015;Mohammadi, Moieni, Hiraga, & Komatsu, 2012;Wang, Cai, Xu, Wang, & Dai, 2016). The role of key genes in growth and development identified in the present study such as E3 ubiquitin-protein ligase, LRX, and protein kinases were supported by earlier studies in different plant species such as Arabidopsis and rice (Draeger et al, 2015;Pokhilko et al, 2011;Wang et al, 2016).…”
Section: Validation Of Candidate Genes Identified From Drought Tolementioning
confidence: 99%